2018
DOI: 10.1111/famp.12396
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation Study of Relationship Checkups as Home Visitations for Low‐Income At‐Risk Couples

Abstract: Couples with the greatest need for relationship health maintenance and intervention are often least able to afford and access it; therefore, accessible, affordable, effective, and brief interventions are needed to improve relationship health for those who need it most. Consequently, this paper examined whether a brief relationship intervention could be effectively implemented with a low‐income, underserved population. All enrolled participants (N = 1,312) received the Relationship Checkup, which consists of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 43 publications
2
66
1
1
Order By: Relevance
“…A promising potential MINC in the content area of the present study is the Relationship Checkup (RC), a brief motivational assessment and feedback intervention (Cordova et al, 2014). A recent open trial of the RC in a large sample of low-income, underserved couples demonstrated that the 90-minute intervention had clinically significant (albeit small) effects on outcomes of interest in the present study (i.e., relationship satisfaction, IPV), with large effects on relationship satisfaction for couples who were in distressed relationships at baseline (Gordon et al, 2019). More than half of the couples in the RC open trial had a child under 18 years of age living in the home, providing a different context for the delivery of the intervention than our sample of couples with a newborn.…”
Section: Implications For Practice and Policymentioning
confidence: 77%
“…A promising potential MINC in the content area of the present study is the Relationship Checkup (RC), a brief motivational assessment and feedback intervention (Cordova et al, 2014). A recent open trial of the RC in a large sample of low-income, underserved couples demonstrated that the 90-minute intervention had clinically significant (albeit small) effects on outcomes of interest in the present study (i.e., relationship satisfaction, IPV), with large effects on relationship satisfaction for couples who were in distressed relationships at baseline (Gordon et al, 2019). More than half of the couples in the RC open trial had a child under 18 years of age living in the home, providing a different context for the delivery of the intervention than our sample of couples with a newborn.…”
Section: Implications For Practice and Policymentioning
confidence: 77%
“…Some participants had already recommended the program to others. Personal referrals are a common way for programs to reach community members and other community-based interventions have found word-of-mouth to be an effective recruitment strategy (e.g., Gordon et al, 2019). Future studies should track how participants heard about the program and whether they made any referrals.…”
Section: Discussionmentioning
confidence: 99%
“…The MC showed effectiveness across some demographics for cisgender couples. Coop Gordon et al (2019) found the MC improved relationship satisfaction across race/ethnicity differences and income differences. The MC was helpful for cisgender heterosexual military couples (Cigrang, 2016), and cisgender lesbian and gay couples Dykeman, 2019, Minten andDykeman, 2020).…”
Section: Marriage Checkup: An Early Intervention To Promote Couple Hementioning
confidence: 99%
“…The MC was helpful for cisgender heterosexual military couples (Cigrang, 2016), and cisgender lesbian and gay couples Dykeman, 2019, Minten andDykeman, 2020). The MC was successfully offered in clinic, home (Coop Gordon et al, 2019), and private practice (Trillingsgaard et al, 2016) settings. No research exists using the MC with transgender couples.…”
Section: Marriage Checkup: An Early Intervention To Promote Couple Hementioning
confidence: 99%